2018
DOI: 10.14419/ijet.v7i2.8.10557
|View full text |Cite
|
Sign up to set email alerts
|

Heart disease prediction using machine learning techniques : a survey

Abstract: Heart related diseases or Cardiovascular Diseases (CVDs) are the main reason for a huge number of death in the world over the last few decades and has emerged as the most life-threatening disease, not only in India but in the whole world. So, there is a need of reliable, accurate and feasible system to diagnose such diseases in time for proper treatment. Machine Learning algorithms and techniques have been applied to various medical datasets to automate the analysis of large and complex data. Many researchers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(73 citation statements)
references
References 14 publications
0
49
0
4
Order By: Relevance
“…Ramalingam et al, used several machine learning algorithms such as support vector machine and naïve Bayes, to name but a few. It shows that the naïve Bayes model was computationally very fast and both the SVM and naïve Bayes performed extremely well [16].…”
Section: Discussionmentioning
confidence: 98%
“…Ramalingam et al, used several machine learning algorithms such as support vector machine and naïve Bayes, to name but a few. It shows that the naïve Bayes model was computationally very fast and both the SVM and naïve Bayes performed extremely well [16].…”
Section: Discussionmentioning
confidence: 98%
“…As per the researches discussed above, still different kind of models are providing variation in the prediction score. Thus, the dimensionality reduction and feature engineering can improve the process of data selection, which ultimately can improve the accuracy estimation [21]. In conclusion, the clear research gap found in the previous researches is that, the measured accuracy is not up to the mark.…”
Section: Machine Learning Classifiers For Heart Disease Predictionmentioning
confidence: 91%
“…V.V. Ramalingam et.al(2018) [2] investigated the prediction of heart disease based on each of the below mentioned algorithms i.e., Naïve Bayes , SVM, Decision Tree ,KNN and concluded by saying that ensemble models have performed extremely well in some cases but poorly in some other cases.Models based on Naïve Bayes classifier were computationally very fast and have also performed well.…”
Section: IImentioning
confidence: 99%